"NAVIGATING RISKS IN INVESTING IN UZBEKISTAN’S INTERNATIONAL TRADE TRANSPORT CORRIDORS" - Shukurov Umidbek Gulomjon Ugli; Kalonov Mukhiddin Bakhritdinovich; Marupov Abdushukurbek Alijonovich (Galaxy International Interdisciplinary Research Journal, 2023)
Uzbekistan’s strategic location as a landlocked country surrounded by five other countries and its abundance of natural resources make it an attractive destination for foreign investors. The government of Uzbekistan has implemented a series of economic reforms aimed at attracting foreign investment in various sectors, including the development of international trade transport corridors. However, investing in Uzbekistan’s international trade transport corridors comes with a variety of risks that investors need to navigate in order to ensure the success of their investments. This paper will explore these risks and provide guidance to investors on how to mitigate them.